If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + 6 = 76 Reorder the terms: 6 + 10y = 76 Solving 6 + 10y = 76 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 10y = 76 + -6 Combine like terms: 6 + -6 = 0 0 + 10y = 76 + -6 10y = 76 + -6 Combine like terms: 76 + -6 = 70 10y = 70 Divide each side by '10'. y = 7 Simplifying y = 7
| 2x-2.5=0.5x-2.5 | | 7x+2x=100 | | 1=n/10+3 | | -x/6-7/5 | | 3(9b-6)-6=6b-3 | | (2x+6)+(2x+1)=4(x+1)+8 | | 11v=10+9v | | -124=-4(1+5x) | | 1/3b^2*4=48 | | (2x-8)+(3x-10)= | | j/6=--1/3 | | 6m+7=13 | | 4x+6y=12y | | -9-9n=-63 | | 118=4x+5x+10 | | -12+5y+7q-2y-5q-21= | | 8+5x=-6+30 | | w^2-22w+121=81 | | -138=-6(7-2v) | | -8-3p=-8(1+8p) | | 8x+3x=8x | | n/3+8=14 | | 129-134= | | 3x-15=X | | -5n-3=-58 | | 18-2g=4j | | 7(4-8r)-r=85 | | N+9=4-5 | | 8X-2(X+9)=X+48 | | 2y+1+4y-3=180 | | F(-2)=2x^2-5x+6 | | 42=2n+8 |